Pentingnya Pengakuan Tanah Kesultanan Terhadap Pembuktian Kepemilikan Hak Atas Tanah - Siregar, Queen Rumata (WARKAT, 2024)
The urgency of moving the Indonesian capital is based on urban carrying capacity so that the state capital is moved from DKI Jakarta to East Kalimantan. The ideal condition where every citizen should be able to independently obtain land rights according to Article 9 paragraph (2) of the UUPA actually causes land disputes between the government and the heirs of the Kutai Kartanegara Ing Martadipura Sultanate who claim IKN land belongs to the heirs, not state land. The purpose of this research is focused on the recognition of sultanate land and the legal status of sultanate land claimed by the heirs of the Kutai Sultanate at the location of the Nusantara Capital City. This research uses the normative juridical method by relying on in-depth problem solving of library materials and relevant legal documents. The results of the study obtained the answer that the recognition of sultanate land claimed by the heirs of the Kutai Sultanate at the location of the Nusantara Capital City is not recognized based on the legal system in Indonesia because the sultanate's legal domain is in the realm of private law so it is necessary to follow the rules of law in the UUPA. It is stated in Dictum IV of the UUPA that the rights of the Swapraja or former Swapraja are abolished and transferred to the state so that there is no recognition of sultanate land. For this reason, the legal status of the Kutai Sultanate land has changed to state land because the heirs of the Kutai Sultanate did not attach a certificate as evidence in court.